The Effect of Financial Performance and Good Corporate Governance on Company Value - Sri Wahyuni, Endah; Karpriana, Angga P.; Indah, Djunita Permata (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to evaluate the effect of financial performance and good corporate governance on company value. Financial performance is assessed using return on assets (ROA), while good corporate governance is measured through the presence of independent commissioners. Company value is measured by Price Book Value (PBV). The data used in this study were collected from eight mining companies listed on the Indonesia Stock Exchange (IDX) over a four-year period (2020-2023). Data analysis was carried out using the panel data regression method. The results of the study indicate that financial performance and board percentage do not have a significant effect on company value. This suggests that these two factors may not be the main indicators that investors need to consider in evaluating company value. This finding is relevant for investors or potential investors, providing an understanding that other aspects, such as business strategy, innovation, and management quality, may play a greater role in investment decision making. This study emphasizes the importance of considering additional factors that are more decisive in analyzing company value to help investors make more informed investment decisions.